2021
DOI: 10.1111/mec.16143
|View full text |Cite
|
Sign up to set email alerts
|

Balanced polymorphism fuels rapid selection in an invasive crab despite high gene flow and low genetic diversity

Abstract: Adaptation across environmental gradients has been demonstrated in numerous systems with extensive dispersal, despite high gene flow and consequently low genetic structure. The speed and mechanisms by which such adaptation occurs remain poorly resolved, but are critical to understanding species spread and persistence in a changing world. Here, we investigate these mechanisms in the European green crab Carcinus maenas, a globally distributed invader. We focus on a northwestern Pacific population that spread acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 100 publications
0
24
0
Order By: Relevance
“…While our data suggest that tidal amplitude plays a major role in both barriers, other environmental drivers could also contribute. Temperature has been shown to play an important role in shaping population differentiation in several crustaceans, such as in American lobster (Benestan et al, 2016) and northern shrimp (Jorde et al, 2015), and a genomic island has been identified in the shore crab which might be associated with rapid temperature adaptation (Tepolt et al, 2021; Tepolt & Palumbi, 2020). The geographical area assessed here is located in the middle of the native distribution of C .…”
Section: Discussionmentioning
confidence: 99%
“…While our data suggest that tidal amplitude plays a major role in both barriers, other environmental drivers could also contribute. Temperature has been shown to play an important role in shaping population differentiation in several crustaceans, such as in American lobster (Benestan et al, 2016) and northern shrimp (Jorde et al, 2015), and a genomic island has been identified in the shore crab which might be associated with rapid temperature adaptation (Tepolt et al, 2021; Tepolt & Palumbi, 2020). The geographical area assessed here is located in the middle of the native distribution of C .…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Molecular Ecology, Tepolt et al (2021) illustrate how the genetic architecture of adaptation and life history influence invasive success. A marvel of many invasive species is that they are incredibly successful despite evolutionary expectations that they will have low adaptive potential and suffer inbreeding depression due to initially small founding population sizes.…”
Section: Biological Invasions Provide Fascinating Examples Of Evolutionmentioning
confidence: 99%
“…Determining the combinations of ecoevolutionary factors that permit this apparent "genetic paradox of invasions" is an ongoing endeavour of invasive species research. Tepolt et al (2021) study the European green crab in its invasive range on the North American west coast. Following a single introduction into California, this crab quickly spread across a wide latitude gradient, despite low diversity in the original founding population.…”
Section: Biological Invasions Provide Fascinating Examples Of Evolutionmentioning
confidence: 99%
See 2 more Smart Citations